Early Childhood Education Based on Life Skills for Street Children in Surabaya - Dessy Putri Wahyuningtyas (Jurusan PGMI FTIK IAIN Metro Lampung, 2019)
Life skills of early childhood consist of personal skills and social skills. In life skills-based education in early childhood is of course related to aspects of child development, namely physical, cognitive, language, social emotional, and spiritual. This research method uses normative research, with the approach used in life skills-based education is a contextual approach. While the methods used are interactive methods, role playing, open discussion and small group activities can also use modeling, observation, situation analysis, one to one rehearsal, debates, and games as a method of theaching life skills. This life skills-based early childhood education program consists of daily living skills and personal or social skills with practical life, sensory, mathematics, language art, and cultural activities that are useful for children’s personal development.